Collagen Structure and Mechanics - Fratzl, Peter; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Collagen: Structure and Mechanics provides a cohesive introduction to collagen-rich tissues, such as tendon, bone, cornea or arterials walls. Written in a clear and didactic manner, this volume reviews current knowledge on hierarchical structure, mechanical properties, deformation and strengthening mechanisms, and discusses many applications in biomaterials and tissue engineering. Researchers in the fields of materials, (bio-)engineering, physics, chemistry and biology will gain an understanding of the structure and mechanical behavior of type I collagen and collagen-based tissues in vertebrates, across all length scales from the molecular (nano) to the organ (macro) level. Collagen: Structure and Mechanics is a reference for new researchers entering this area and can serve also as a basis for lecturing in the interdisciplinary field of biological materials science.
Collagen: Structure and Mechanics, an Introduction -- Collagen Diversity, Synthesis and Assembly -- Collagen Fibrillar Structure and Hierarchies -- Restraining Cross-Links Responsible for the Mechanical Properties of Collagen Fibers: Natural and Artificial -- Damage and Fatigue -- Viscoelasticity, Energy Storage and Transmission and Dissipation by Extracellular Matrices in Vertebrates -- Nanoscale Deformation Mechanisms in Collagen -- Hierarchical Nanomechanics of Collagen Fibrils: Atomistic and Molecular Modeling -- Mechanical Adaptation and Tissue Remodeling -- Tendons and Ligaments: Structure, Mechanical Behavior and Biological Function -- Collagen in Arterial Walls: Biomechanical Aspects -- The Extracellular Matrix of Skeletal and Cardiac Muscle -- The Cornea and Sclera -- Collagen and the Mechanical Properties of Bone and Calcified Cartilage -- Dentin -- Genetic Collagen Diseases: Influence of Collagen Mutations on Structure and Mechanical Behavior -- Biomimetic Collagen Tissues: Collagenous Tissue Engineering and Other Applications.
Keywords: Engineering; Proteomics; Biophysics; Biological physics; Medical physics; Radiation; Continuum mechanics; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Medical and Radiation Physics; Biomaterials; Biophysics and Biological Physics; Continuum Mechanics and Mechanics of Materials; Proteomics; Electronic books